Begijnen in Brabant : de begijnhoven van Breda en Diest - Koorn, Florence W. J. (Florence Wilhelmina Johanna), 1951-2008; Diepraam, Joh.; Meeter, Onno, 1939-2004; Van der Eycken, Michel (Michel Modeste), 1950- ('s-Gravenhage : Nijgh & Van Ditmar, 1987)
Historische schets.
Uitg. van Esso Nederland.
Met lit. opg.
Keywords: 1159 church history, history of doctrine: other; 2170 religious architecture; Begijnen; Begijnhoven; Beguinages -- Belgium -- Diest; Beguinages -- Netherlands -- Breda; Beguinages; Belgium -- Diest; Breda (Netherlands) -- Church history; Breda (stad).; Diest (Belgium) -- Church history; Diest; Netherlands -- Breda; Church history; Geschiedenis (vorm).